2008
DOI: 10.1590/s0100-83582008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da luz e da temperatura na germinação de Alternathera tenella, Conyza bonariensis e Digitaria ciliaris

Abstract: RESUMO -Este trabalho teve o objetivo de avaliar a influência da luz e da temperatura na germinação de três espécies de plantas daninhas comuns em lavouras brasileiras. As espécies estudadas foram Alternanthera tenella, Conyza bonariensis e Digitaria ciliaris, nas quais se testou a influência de quatro variações de temperatura (15/25, 20/30, 20/35 e 30/ 40 °C), com e sem a presença de luz, no percentual de germinação e no índice de velocidade de germinação (IVG). As sementes foram coletadas em canteiros experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 13 publications
1
15
0
6
Order By: Relevance
“…Maia et al (2004), studying weed seed banks in natural fields, also observed that soil moisture content was one the most important abiotic factors affecting the patterns of vegetation. Other authors have also cited soil water content as a determinant of weed seed bank germination (Munhoz & Felfili 2006;Vivian et al 2008). In our ex situ study, the seeds were further protected by the removal of weed seedlings from the trays after the assessments, which eliminated competition, and by the fact that we controlled abiotic factors such as air relative humidity, light and temperature.…”
Section: Discussionmentioning
confidence: 91%
“…Maia et al (2004), studying weed seed banks in natural fields, also observed that soil moisture content was one the most important abiotic factors affecting the patterns of vegetation. Other authors have also cited soil water content as a determinant of weed seed bank germination (Munhoz & Felfili 2006;Vivian et al 2008). In our ex situ study, the seeds were further protected by the removal of weed seedlings from the trays after the assessments, which eliminated competition, and by the fact that we controlled abiotic factors such as air relative humidity, light and temperature.…”
Section: Discussionmentioning
confidence: 91%
“…Maia et al (2004), studying weed seed bank in natural fields observed that soil moisture content was the most imporant abiotic factor affecting patterns of vegetation variation. Other authors also consider soil water content as a determinant factor affecting weed seed bank germination (Munhoz & Felfili, 2006;Vivian et al, 2008). Moreover, withdrawal of weed seedlings from trays after assessments carried out in the greenhouse decreased the effect of competition which is generally lower at the weed seedling phase.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous factors affect weed seed germination including variations in soil temperature and moisture (Begum et al, 2006;Hérault & Hiernaux, 2004;Maia et al, 2004), light intensity (Vivian et al, 2008;Batlla & Benech-Arnold, 2014) and physiological aspects of the seeds particularly seed dormancy (Baskin & Baskin, 2006). When favorable environmental conditions occur and physiological constraints are overcome, seeds germinate; weeds grow and produce new propagules enriching the soil seed bank.…”
Section: Introductionmentioning
confidence: 99%
“…The following variables were evaluated: remaining seeds; germination at first and second count, 7 and 14 days after sowing (DAS) (Vivian et al, 2008); abnormal seedlings; dead seeds; and dormant seeds at 14 DAS. The percentage of remaining seeds was calculated based on the initial number of seeds per replication, while for germination percentages, abnormal seedlings, dead and dormant seeds, were estimated based on the number of remaining seeds.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, weed seeds germinate when conditions are favorable, in soils with enough resources to support the subsequent growth of the plant and thus achieve the survival of the species (Chauhan et al, 2008). Thus, factors such as light become decisive in positively photoblastic seeds, such as horseweed, which require the incidence of a certain quantity and quality of light to start the germination process (Vidal et al, 2007;Vivian et al, 2008;Yamashita et al, 2016).…”
Section: Introductionmentioning
confidence: 99%